Mediatized Humanitarianism: Trust and Legitimacy in the Age of Suspicion - Vestergaard, Anne (Journal of business ethics, 2014)
The article investigates the implications of mediatization for the legitimation strategies of humanitarian organizations. Based on a (full population) corpus of ~400 pages of brochure material from 1970 to 2007, the micro-textual processes involved in humanitarian organizations’ efforts to legitimate themselves and their moral claim were examined. A time trend analysis of the prioritization of actors in the material indicates that marked shifts in legitimation loci have taken place during the past 40 years. A discourse analysis unfolds the three dominant discourses behind these shifts, namely legitimation by accountancy, legitimation by institutionalization, and legitimation by compensation. The analysis relates these changes to a problem of trust associated with mediatization through processes of mediation.